2020
DOI: 10.1038/s41598-020-73901-8
|View full text |Cite
|
Sign up to set email alerts
|

Tuning magnetic properties of penta-graphene bilayers through doping with boron, nitrogen, and oxygen

Abstract: Penta-graphene (PG) is a carbon allotrope that has recently attracted the attention of the materials science community due to its interesting properties for renewable energy applications. Although unstable in its pure form, it has been shown that functionalization may stabilize its structure. A question that arises is whether its outstanding electronic properties could also be further improved using such a procedure. As PG bilayers present both sp$$^2$$ 2 and sp$$^3$$ 3 carbon planes, it consists of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…28 Tuning magnetic properties of PG bilayers through doping with boron, nitrogen, and oxygen have been studied. 29 As PG bilayer presents both sp 2 and sp 3 carbon planes, it consists of a flexible candidate for functionalization tuning of electromagnetic characteristics. It has been observed the emergence of different magnetic characteristics when boron and nitrogen were used as dopant species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Tuning magnetic properties of PG bilayers through doping with boron, nitrogen, and oxygen have been studied. 29 As PG bilayer presents both sp 2 and sp 3 carbon planes, it consists of a flexible candidate for functionalization tuning of electromagnetic characteristics. It has been observed the emergence of different magnetic characteristics when boron and nitrogen were used as dopant species.…”
mentioning
confidence: 99%
“…In the case of doping with oxygen, the rupture of bonds in the sp 2 planes has not induced a magnetic moment in the material. 29 The mechanics of PG with vacancy defects under large amplitude tensile and shear loading has been investigated using molecular dynamics simulations. 30 The results showed that defective PG has a plastic behavior similar to pristine PG, which is caused by the irreversible pentagon-to-polygon structural transformation occurring during tensile and shear loading.…”
mentioning
confidence: 99%